Improving the accuracy of determining orientation of a rapidly rotating object - Nekrasova, Mariia; Uspenskyi, Valerii (Eastern-European Journal of Enterprise Technologies, 2016)
We developed a method for improving correction by the excess information of parameters of orientation of the object that rotates rapidly around the longitudinal axis. To control the motion of such an object, it is necessary to determine with high frequency and use the information on its triaxial orientation in space. In a general case this is achieved by using a platform-free inertial navigation system. The specificity of the object that rotates rapidly is the fact that the error of determining orientation is quickly accumulated in such a system, which us connected to error of the so-called scale coefficient for gyroscope and is proportional to the angle of rotation relative to its measuring axis. This leads to the fact that it becomes impossible while determining the control to use information regarding orientation by the factor of its unreliability. To solve this problem, we developed a method of correction of orientation of the object that rotates rapidly, devoid from the mentioned disadvantages. Underlying this method is a high-frequency correction of angle of heel based on the use of measurements of vector of imaginary acceleration, the projections of which onto the axes of sensitivity of accelerometers, as a result of rotation, have modulated character. To increase accuracy of determining the angle of heel, we propose, with the frequency of rotation of the object increased by four times, to perform correction of its value by the readings of accelerometers. By registering the passage by the series of measurements of its local maximum or local minimum, the correction signal is formed, which corresponds to the true value of the angle of heel 0, π, 3/2π or 1/2π. This method may be used to create high-precision systems of motion control.